Long Non-Coding RNA-Mediated Competing Endogenous RNA Networks in Ischemic Stroke: Molecular Mechanisms, Therapeutic Implications, and Challenges - Shuxia Zhang; Shuxia Zhang; Shuxia Zhang; Shuxia Zhang; Shuxia Zhang; Ting Zhu; Qiaoyu Li; Qiaoyu Li; Qiaoyu Li; Qiaoyu Li; Qiaoyu Li; Guibo Sun; et al. (Frontiers Media S.A., 2021)
Ischemic stroke (IS) is a disease that is characterized by high mortality and disability. Recent studies have shown that LncRNA-mediated competing endogenous RNA (ceRNA) networks play roles in the occurrence and development of cerebral I/R injury by regulating different signaling pathways. However, no systematic analysis of ceRNA mechanisms in IS has been reported. In this review, we discuss molecular mechanisms of LncRNA-mediated ceRNA networks under I/R injury. The expression levels of LncRNAs, microRNAs (miRNAs), and messenger RNAs (mRNAs) and their effects in four major cell types of the neurovascular unit (NVU) are also involved. We further summarize studies of LncRNAs as biomarkers and therapeutic targets. Finally, we analyze the advantages and limitations of using LncRNAs as therapeutics for IS.